Case Report: Intra-aortic balloon pump in a patient with refractory cardiogenic shock complicating severe aortic stenosis—enhanced hemodynamic response with low aortic compliance - Ota, Issei; Sawada, Kenichiro; Saku, Keita; Noguchi, Teruo (Frontiers in Cardiovascular Medicine, 2025)
Intra-aortic balloon pump (IABP) counterpulsation generates pressure changes that are primarily influenced by aortic compliance, an index of arterial elasticity that varies widely among patients with cardiovascular disease. However, the potential role of aortic compliance in determining IABP efficacy remains poorly understood. We present the case of an 80-year-old man with severe aortic stenosis and pneumonia who was admitted with generalized fatigue and worsening dyspnea. He developed refractory Society for Cardiovascular Angiography & Interventions stage D cardiogenic shock despite multiple vasopressors. In this patient, who had low aortic compliance (0.62–0.81 ml/mmHg), IABP initiation resulted in immediate hemodynamic improvement through enhanced diastolic augmentation and systolic unloading, leading to rapid reversal of both hypoperfusion and pulmonary congestion. Following successful weaning from vasopressors and IABP removal, the patient underwent transcatheter aortic valve replacement without temporary mechanical circulatory support-related complications. The notable hemodynamic improvement observed in this case highlights the potential importance of aortic compliance as a key determinant of IABP efficacy in elderly patients with cardiogenic shock, suggesting that aortic compliance may help optimize patient selection for IABP support.